Netrin-1 is associated with macrophage infiltration and polarization in human epicardial adipose tissue in coronary artery disease. Issue 6 (June 2017) - Gurses, Kadri Murat; Ozmen, Fusun; Kocyigit, Duygu; Yersal, Nilgun; Bilgic, Elif; Kaya, Erkan; Kopru, Cagla Zubeyde; Soyal, Tolga; Doganci, Suat; Tokgozoglu, Lale; Korkusuz, Petek
Abstract: Background: Inflammatory activity originating from the epicardial adipose tissue (EAT) may have a role in coronary artery disease (CAD) pathogenesis. The relationship between macrophage infiltration, polarization in the EAT, and netrin-1 gene expression was investigated. Methods: Macrophage infiltration and polarization were examined by immunohistochemical methods and expression levels of netrin-1, Unc5b, and cytokines related with M1-macrophage subtype (IL-12 and IL-18) were determined by quantitative polymerase chain reaction in subcutaneous and epicardial adipose tissue obtained from patients undergoing coronary artery bypass grafting and non-coronary cardiac surgery. Results: CAD patients had higher CD68+ ( p  = 0.005) and CD11c+ ( p  < 0.001) macrophage count in EAT when compared to the controls. CD11c+/CD206+ macrophage ratio, which reflects dominancy of M1-macrophage phenotype, was significantly increased in EAT of CAD patients when compared to that of the controls ( p  = 0.008). CAD patients had significantly higher netrin-1, Unc5b, and IL-18 gene expression in the EAT when compared to the control group ( p  < 0.001, p  < 0.001, and p  = 0.006 respectively). Increased macrophage infiltration and polarization were associated with higher netrin-1, Unc5b, and IL-12 gene expression in EAT ( p  < 0.05). Conclusions: Findings suggest a link between enhanced netrin-1 expression in EAT and macrophage infiltration and polarization in patients with CAD.